Cellular functionality on nanotubes of Ti-30Ta alloy - Capellato, Patricia [UNESP]; Smith, Barbara S; Popat, Ketul C.; Alves Claro, Ana P. R. [UNESP] (Trans Tech Publications, 2015)
Recent studies have identified strong correlations between anodized metals and the production of highly biomimetic nanoscale topographies. These surfaces provide an interface of enhanced biocompatibility that exhibits a high degree of oxidation and surface energy. In this study, Human dermal fibroblasts (HDF, neonatal) were utilized to evaluate the biocompatibility of Ti-30Ta nanotubes after 1 day of culture. The anodization process was performed in an electrolyte solution containing HF (48%) and H2SO4 (98%) in the volumetric ratios 1:9 with the addition of 5% dimethyl sulfoxide (DMSO) at 35V for 40 min. Cellular analysis identified improved fibroblast functionality on the nanotube surface, showing increased elongation, and extracellular matrix production on the Ti-30Ta nanotubes. The results presented identify improved cellular interaction on Ti-30Ta nanotubes as compared to the control substrates. Thus, the formation of the nanotube on Ti30Ta alloy may have potential application as interface for implantable devices.
Keywords: Human dermal fibroblasts; Ti-30Ta nanotube arrays